A prospective study to analyse the surgical outcome of posterior acetabular fractures - Basha, Shaik Masthan; Divya, Vurundhur (International Journal of Research in Orthopaedics, 2019)
Background: Fractures of acetabulum are relatively uncommon, but because they involve major weight bearing joint in the lower extremity, they assume great clinical importance. Acetabular fractures are still difficult fractures to manage and are a major challenge to treating orthopaedic surgeon. The present study was aimed to study the surgical outcome of posterior acetabulum fractures and postoperative complications and failures. Methods: A one year prospective study was done after ethical approval. Patients with traumatic injury and posterior acetabular fracture was included and categorized according to the Letournel-Judet classification. Kocher-Langenbeck approach was used for all the cases and clinical follow-up and radiological evaluation was done up to 12 months. Evaluation of different demographic elements with reference to Harris hip score was also carried out. Statistical analysis was performed using the Statistical Package for the Social Sciences software. Results: Twenty cases with mean age 42.6 years and males 65% were included. Road traffic accident was cause in 65% of cases.50% of the cases had good, 20% excellent, 25% fair and 5% poor outcome in our study by Harris Hip scoring. Two cases of superficial infection, one deep infection, iatrogenic sciatic nerve injury in one, heterotopic ossification in one and one case of intra-articular screw penetration was observed. Conclusions: Operative treatment of displaced acetabular fractures gives satisfactory functional results. Thorough evaluation of radiograph/ CT scan and a proper pre-operative planning is necessary for decision making regarding an appropriate surgical approach, the appropriate type of implant and fixation.